Relationship Between Knowledge And Personal Hygiene With Behavior Prevention Of Dermatitis Contact In Fishermen In The Working Area Of The Beringin Raya Community Health Center Bengkulu City In 2025 - Amanda, Dea Susita; Handayani, Tita Septi; Tranado, Hengki (Student Scientific Journal, 2025)
The skin is an organ that separates the body from the external environment, the skin is continuously exposed to environmental factors. According to (WHO) the level of infectious skin diseases worldwide was reported to be around 300 million cases in 2020. The purpose of this study was to determine the relationship between knowledge and personal hygiene with the behavior of preventing contact dermatitis in fishermen in the working area of the Beringin Raya Health Center, Bengkulu City in 2025. The method used was descriptive quantitative with a cross-sectional approach. The sampling technique used total sampling with the number of samples in this study 48 respondents in fishermen in the working area of the Beringin Raya Community Health Center, Bengkulu City in 2025, The results showed that almost most of the respondents had insufficient knowledge, almost all respondents had poor personal hygiene, most of the respondents had poor dermatitis prevention behavior. And there is a significant relationship between knowledge and contact dermatitis prevention behavior in fishermen in the working area of the Beringin Raya Community Health Center, Bengkulu City in 2024 where the p value is (0.010), There is a significant relationship between personal hygiene and contact dermatitis prevention behavior in fishermen in the working area of the Beringin Raya Community Health Center, Bengkulu City in 2025 where the p value is (0.00). This study is expected to provide a source of information to community health centers to consider more about preventing contact dermatitis in fishermen.